THE POLICY CYCLE APPROACH IN SPECIAL EDUCATION CONTEXT - Shoiti Nozu, Washington Cesar; Garcia Bruno, Marilda Moraes [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This paper takes a method of analysis entitled policy cycle suggested by both English researchers Stephen J. Ball and Richard Bowe and largely disclosed in Brazil by Jefferson Mainardes, who applies it in special education context. Policy cycle approach foresees the analysis of five contexts: influence, text production, practice, outcomes/effects and political strategy. However, this study is limited by understanding a policy cycle in Brazilian special education in three contexts. First, influence is the constitution of inclusion discursiveness in the field of special education. Second, the text production context ranks normative-policy texts which represent the current special education policy in an inclusive education perspective and highlight a specialized educational service. And finally practice is the performance of the specialized educational service in Multifunctional Resource Classroom.
Keywords: Educational Policy; Inclusive Education; Specialized Educational Service; Multifunctional Resource Classroom